Changes in Secondary Healthcare Use Over Retirement Transition: Examining Social Differences With Swedish Register Data - Wetzel, Martin; König, Stefanie; Kelfve, Susanne (Frontiers in Sociology, 2022)
Background: Despite its relevance for healthcare expenditures and public health, few studies have examined how secondary healthcare use changes during the retirement transition. We therefore use Swedish register data to examine whether retirement is associated with intensified secondary healthcare use overall and for specific subgroups based on gender and education. Methods: The sample was all individuals registered in Sweden who retired from paid work in 2010. We used Generalized Estimating Equations models to analyse changes in two indicators of secondary healthcare use, namely specialist visits and hospitalisation, from three years prior to five years after retirement. Results: Retirement is not associated with changes in specialist visits or hospitalisation per se. Three years before retirement, women were more likely to visit a specialist but less likely to be hospitalized than men; these gender differences disappeared approximately one year before retirement. Women with high education were more likely to visit a specialist than women with low education across the entire retirement transition, particularly post-retirement. Significant differences with regard to specialist visits between male educational groups only emerged twelve months after retirement. There were no educational differences with regard to hospitalisation. Conclusions: We conclude that secondary healthcare use in Sweden does not generally change with retirement. However, over the course of retirement gender differences in secondary healthcare use tend to decrease and within-gender educational differences tend to increase. We interpret the results as reflecting the role of labour market institutions in contributing to gender differences but repressing educational differences in secondary healthcare use.